Usama Ibn Munqidh : Warrior Poet of The Age of Crusades - Cobb, Paul M., 1967- (London Oneworld Publication, 2009)
A fascinating portrait of Usama ibn Munquidh, the famed 12th century warrior-poet and chronicler of everyday Muslim in the era of the first Crusade.
Include Map and Index
Keywords: Soldiers -- Syria -- Islamic Empire